An overview of QOL studies in Malaysia: present trends and future directions - Mohit, Mohammad Abdul (2014)
Quality-of-life (QOL) is a multifaceted concept and it has attracted the attention of researchers from a wide range of academic disciplines as well as interest among policy makers, planners and others in the environmental design fields. Being a rich concept, QOL studies can be construed in different perspectives like health approach, needs approach, happiness versus life satisfaction and the resource management approach. Although QOL research in Malaysia started in 1987, progress is slow. This paper provides an overview of the present trends of QOL research by highlighting the disciplinary and spatial bias and finally, suggests future directions of QOL research in Malaysia.